Students’ Perspectives on Speaking Anxiety in the English Foreign Language Classroom - Aulia Nisa Khusnia (Ahmad Dahlan Journal of English Studies, 2016)
Anxious students are often concerned about the impressions that others form of them. When such students are confronted in a classroom with a learning situation that makes them uncomfortable, they may choose to withdraw from the activity. Some learners believe they cannot perform in English and consequently form negative expectations, which in turn lead to decreased effort and the avoidance of opportunities to enhance their communication skills. The goal of this study was to identify those factors, as perceived by students, that may contribute to anxiety, and those factors that may reduce anxiety in an attempt to understand more fully the role that anxiety may play in learning a foreign language.Â